Pendeteksi Gempa Dengan Metode FM Berbasis Personal Computer - Jamal, Zaidir (Jurnal Informatika, 2011)
Generally, earthquake is measured with a seismometer, a device which is also known as seismograph Â that works based onÂ  detection of seismic wave in earthâs crust.Â  This research designs and implements an earthquake detection using frequency modulation method based on personal computer.Â  The research results a system and simulation. Simulation shows that in a normal condition the strength carrier is 2,5 % and before the earthquake occurred, the strength carrier is 55%. Frequency modulation method can be implementedÂ  to detect earthquake by building some measurement stations at severalÂ Â  places. Keyword : earthquake, frequency modulation, seismograph